Basic measurements of radiation at station Fort Peck (1995-01 et seq) - John Augustine; John Deluisi (PANGAEA, 2025)
This is a compilation of all short-wave and long-wave radiation datasets from Fort Peck that were and are published in the frame of BSRN. New data will be added regularly. The data are subject to the data release guidelines of BSRN (https://bsrn.awi.de/data/conditions-of-data-release/).